Kehandalan Model Altman Z-score dalam Memprediksi Kebangkrutan Perusahaan-Perusahaan yang Terdapat di Bursa Efek Indonesia Periode 2005 – 2010 - Prayanthi, Ika (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
The purpose of this research is to prove the reliability of the Altman Z-score in predicting bankruptcy for one to two years after prediction by comparing proportion of predicted company bankrupt with proportion of actual company bankrupt. This empirical study is done to manufacture and non manufacture company in Indonesian Stock Exchange over the period 2005 – 2010. This research used purposive sampling method. As a result all public companies are chosen as sample except banking, financing and merger company. Whereas in collecting data, this research analyzed secondary data obtained from Indonesian Stock Exchange. The measurement used is the binomial test of proportion with computer application program. Analysis result showed that value of Z binomial > 1.96. It means that there are significant differences between the proportion of predicted company bankrupt with proportion of actual company bankrupt. Thereby, Altman Z-score is not reliable in predicting bankruptcy for manufacture and non manufacture company in Indonesian Stock Exchange especially for one to two years after prediction.